UTILIZATION OF TOLL ROAD SECTIONS AS STATE PROPERTY FOR MAXIMIZING PUBLIC WELFARE - Heru Sugiyono; Dwi Aryanti Ramadhani (Kanun Jurnal Ilmu Hukum, 2023)
This study examines the usage of toll road sections that have fully recovered their investment as state-owned assets, and evaluate the compatibility of the Toll Road Concession Agreement (Perjanjian Pengusahaan Jalan Toll/PPJT) about granting concessions for the operation of these toll road sections that have paid off their investment. This research employs a normative juridical method, analyzing relevant literature on using toll road sections that have reached the return on investment as state-owned assets. The findings indicate that the State's utilization of these toll road sections does not uphold justice, as it fails to maximize the community's welfare. The PPJT on the concession of operating toll road sections that have paid off their investment differs from the utilization of state-owned assets as stipulated by existing regulations due to the imposition of general contributions and profit sharing. It is the government to consider the concession agreement to include toll road sections that have completed their investment to return into the government for maximizing public welfare.